2010
DOI: 10.1111/j.1365-2125.2009.03595.x
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin can be used effectively as a positive control in thorough QT/QTc studies in healthy volunteers

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• New drugs are expected to undergo rigorous clinical electrocardiographic evaluation ('thorough QT/QTc study') during their early clinical development in order to determine any affect on cardiac repolarization. • The fluoroquinolone antibiotic moxifloxacin (400 mg) has been used as a positive comparator for thorough QT/QTc studies due to its QT prolongation (QTcF) of between 6 and 10 ms. • Positive comparators that are able to produce mean changes close to the regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 26 publications
(52 reference statements)
7
33
0
1
Order By: Relevance
“…Moxifloxacin has been used as an active control drug in previous QT/QTc studies, which indicated that even a single 400 mg dose of moxifloxacin was associated with a significant increase of QT/QTc . In this study, the largest mean difference of ΔQTcF between moxifloxacin and placebo was 13.6 milliseconds with 90% CI of 11.2 and 15.9 milliseconds, which was in good accordance with those of previous reports .…”
Section: Discussionsupporting
confidence: 92%
“…Moxifloxacin has been used as an active control drug in previous QT/QTc studies, which indicated that even a single 400 mg dose of moxifloxacin was associated with a significant increase of QT/QTc . In this study, the largest mean difference of ΔQTcF between moxifloxacin and placebo was 13.6 milliseconds with 90% CI of 11.2 and 15.9 milliseconds, which was in good accordance with those of previous reports .…”
Section: Discussionsupporting
confidence: 92%
“…There have been several reports that levofloxacin is associated with corrected QT (QTc) prolongation [20-22]. However, some study has reported that there is no effect of levofloxacin on QTc prolongation [23].…”
Section: Introductionmentioning
confidence: 99%
“…According to other investigations [87] and RCTs [23,79,[83][84][85] here reported, among the molecules still in clinical use, moxifloxacin accounts for the highest risk of prolonging QT interval. More interestingly, the most recent pharmacovigilance survey [67] confirmed that TdP were more disproportionally reported for moxifloxacin than levofloxacin and ciprofloxacin.…”
Section: Discussionmentioning
confidence: 46%
“…Hence, although papers published since 1995 were included in this literature search, the novelty of AEs due to ciprofloxacin and levofloxacin were prioritized among medical journals. The same explanation could be applied for the higher number of cases related to ciprofloxacin compared with levofloxacin, since also the latter had been associated with a high risk of QT prolongation [82] Double-blind, placebo-controlled, crossover 50 healthy subjects Levofloxacin 500 mg, 1000, 1500 mg vs placebo QTc prolongation 4 days Levofloxacin 1500 mg vs placebo (p < 0.05) [83] Prospective, randomized, double- --2.1) [84] Randomized, open-label crossover 13 healthy subjects Ciprofloxacin 500 mg, (i.e., moxifloxacin) [10,15,16,23,79,[83][84][85]. Moreover, the use of ciprofloxacin has shown a growing trend across the last decades in both European and extra European countries [88,89] so partly explaining the major number of events being collected for this molecule.…”
Section: Discussionmentioning
confidence: 99%